Pulmonary arterial hypertension in patient treated for multiple sclerosis with 4‐aminopyridine. (15th July 2018) - Ribeiro Baptista, Bruno; Petitpain, Nadine; Gomez, Emmanuel; Yelehé‐Okouma, Melissa; Valentin, Simon; Guillaumot, Anne; Chabot, François; Chaouat, Ari
Abstract: 4‐Aminopyridine (4‐AP) is a recent treatment indicated to improve walking in patient with multiple sclerosis. We report the first case of pulmonary arterial hypertension (PAH) that we attribute to the use of 4‐AP. A 64‐year‐old woman with multiple sclerosis presented with dyspnea. After excluding other secondary causes of pulmonary hypertension, a diagnosis of severe PAH due to 4‐AP was made based on right heart catheterization. History revealed that the dyspnea began with the initiation of 4‐AP. After discontinuation of 4‐AP therapy and initiation of ambrisentan and tadalafil, dyspnea and pulmonary arterial pressure have improved significantly and one specific PAH treatment was stopped. 4‐AP is an outward rectifying potassium channel blocker with a vasoconstrictor effect in animal's pulmonary artery. According to the chronological sequence of events, the lack of other etiology, and its pharmacological plausibility, 4‐AP is highly suspected to have induced our patient's PAH.